Sociological aspects of management and behaviour compliance with security policies – the role of employees’ security awareness in purpose industry - Tokalić, Vladimir; Tomašević, Vladimir; Raut, Jelena (Sociološki pregled, 2025)
In the digital age, information security is gaining greater importance, especially in dedicated industry. This study investigates the relationship between leadership styles and employees’ behaviour compliance with security policies. The aim of the study is to analyze the indirect effect of transformational leadership on employee compliance with security policies, through the benefits of employees’ security countermeasure awareness. The HBM model, adapted to dedicated industry, was used. The study involved 300 respondents from four companies. Dependencies between leaders’ motivation and employees’ awareness of security countermeasure effectiveness were identified. The results indicate key points for improvement, emphasizing continuous education and motivation of leaders in building a security culture, which is essential for success in international trade in precision mechanics.